Composição e distribuição dos Crustácea (Decapoda) na Lagoa do Peixe, Rio Grande do Sul, Brasil - Santos, Sandro (2000)
The Lagoa do Peixe (Peixe's Lagoon) is located between Atlantic Ocean and Lagoa dos Patos and is 30 Km long and 0,5-2,0 Km wide (31º13'S, 50º55'W -31º26'S, 51º09'). For one year, the composition and distribution of Crustácea Decapoda were analyzed monthly (from July/1994 to June/1995), in seven subareas (terrestrial border and aquatic area) and physical and chemical parameters (depth, salinity, sediment texture, oxygen in water, organic material of sediment and water temperature) were registered. Decapoda from the families Grapsidae, Ocypodidae, Portunidae (Brachyura), Diogenidae (Anomura) and Penaeidae (Penaeidea) were captured. Chasmagnathus granulata Dana 1851 was found ali months near the canal connecting Atlantic Ocean and Lagoa do Peixe, but inside the lagoon it was collected only in October/94 and June/95, and in extreme subareas it was sampled in February/95 when the salinity was 31 at these sites. Callinectes sapidus Rathbun, 1896 and Cyrtograpsus angulatus Dana, 1851 were captured throughout the year, except October/94 and April/95, respectively. Both species were found in ali áreas of sample, indicating a high plasticity in relation to the factors analyzed in this study. Another species captured probably come in the lagoon in specific months, when the environment provides ideal conditions for their develo-pments.